Implementasi Enkrip Dan Dekrip File Menggunakan Metode Advance Encryption Standard (AES-128) - Melenia Bayu Aryanto; Muhlis Tahir; Silvia Irma Devita; Zuda Nuril Mustofa; Qurrotun Ainiyah; Shelviatus Sundoro (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
Data security refers to the confidentiality of information exchanged, especially when the data is on a computer network that is connected to other networks. Of course, this is risky when irresponsible individuals gain access to confidential or valuable information. To avoid the undesired possibility of damage or loss leading to significant material loss. To solve this problem, you need a security system that helps encrypt and decrypt data files. Cryptography is the study of cryptography in which plaintext is encrypted with an encryption key and transformed into a script that is difficult for others to read without the decryption key. Cipher sare class ified intot wotypes. classic and modern. Classical encryption works in character mode using the alphabet (A-Z) and the algorithms used are simple enough to easily break the ciphertext, while modern algorithms use ASCII (American Standard Code for Information It is formed using binary bits (0's and 1's) derived from the Interchange. Creating a key is so complicated that knowing the key makes it difficult to guess the ciphertext. In this study, we create a cryptographic application that uses the 128-bit Advanced Encryption Standard (AES) encryption algorithm. The programming language is PHP and uses MySQL as the web application print and database. Files uploaded for encryption are stored in the database. It is expected that students will be able to maintain the security of their file data with the help of this application.